Occupational Engagement Scale–Student: Development and Initial Validation. (February 2015) - Cox, Daniel W.; Krieshok, Thomas S.; Bjornsen, Abby L.; Zumbo, Bruno D.
The Occupational Engagement Scale–Student (OES-S)—a 9-item measure of occupational engagement in college students—was developed and initial validity evidence is presented. Using two samples of college students, exploratory and confirmatory factor analyses supported the measure's unidimensionality. Criterion validity was supported via the OES-S predicting (a) vocational identity, (b) academic major satisfaction, (c) gains in personal development, (d) gains in vocational competence, and (e) gains in general education. Implications for practice, theory, and future research are discussed.